PENGELOLAAN DAN PENGEMBANGAN GALANGAN KAPAL KAYU; STUDI KASUS GALANGAN KAPAL PELABUHAN BARU DI BAGANSIAPIAPI KABUPATEN ROKAN HILIR PROVINSI RIAU - Farhan Ramdhani; Viktor Amrifo; Nofrizal Nofrizal; Femi Riza (Berkala Perikanan Terubuk, 2020)
The problems faced by this shipyard were the insufficient land to increase the ship production, and theinsufficient number of workers so that it took a long time to produce one ship which resulted in piling upof the ship orders at this shipyard. Moreover, it was difficult to obtain the license to export the shipsabroad. This study was conducted from June 20th to July 4th. This study was located at the Shipyard ofthe New Bagansiapiapi Harbor, Rokan Hilir Regency, Riau Province. The data obtained were analyzed byusing a descriptive analysis and to know the development the data were analyzed by using SWOTanalysis. This shipyard had low technology and was managed by using a family management system.Based on the SWOT analysis carried out by the New Harbor Shipyard, it can still be developed because itwas in a 1.01 quadrant. The strategic plans for the development of the shipyard of the new Harbor wereholding a training for the timber shipbuilders to build FRP ships, attending an entrepreneurship training inthe management of the shipyard industry for shipyard owners, and collaborating with stakeholders such asthe government, raw material supply companies, training and education fields (college) to be able todevelop the New Harbor Shipyard.